PENDIDIKAN KARAKTER - Adang Heriawan (JPsd (Jurnal Pendidikan Sekolah Dasar), 2015)
Character education emphasizes the ethical-spiritual dimension in the process of personal formation. Character education is triggered by a German pedagogue FW Foerster (1969-1966), which was a reaction to stagnation and natural pedagogy Rousseauian and Deweyan pedagogical instrumentalism. Moreover, pedagogy puerocentris through the celebration of the spontaneity of children (Édouard Claparède, Ovide Decroly, Maria Montessori) that characterizes Europe and the United States early 19th century increasingly considered no longer sufficient for the intellectual and cultural formation of a person. Keywords : Character education